Dysregulation of endothelial nitric oxide synthase does not depend on hemodynamic alterations in bicuspid aortic valve aortopathy - Gauer, Simon; Henn, Dominic (Journal of the American Heart Association, 2020)
BackgroundBicuspid aortic valves (BAVs) predispose to ascending aortic aneurysm. Turbulent blood flow and genetic factors have been proposed as underlying mechanisms. Endothelial nitric oxide synthase (eNOS) has been implicated in BAV aortopathy, and its expression is regulated by wall shear stress. We hypothesized that if turbulent flow induces aneurysm formation in patients with a BAV, regional differences in eNOS expression would be observed in BAVs.Methods and ResultsAscending aortic specimens were harvested intraoperatively from 48 patients with tricuspid aortic valve (19 dilated, 29 nondilated) and 38 with BAV (28 dilated, 10 nondilated) undergoing cardiac surgery. eNOS mRNA and protein concentration were analyzed at the convex and concave aortic wall. In nondilated aortas, eNOS mRNA and protein concentration were decreased in BAV compared with tricuspid aortic valve (all P<0.05). eNOS expression was increased in association with dilation in BAV aortas (P=0.03), but not in tricuspid aortic valve aortas (P=0.63). There were no regional differences in eNOS mRNA or protein concentration in BAV aortas (all P>0.05). However, eNOS expression was increased at the concave wall (versus convexity) in tricuspid aortic valve dilated aortas (all P<0.05).ConclusionsDysregulated eNOS occurs independent of dilation in BAV aortas, suggesting a potential role for aberrantly regulated eNOS expression in the development of BAV‐associated aneurysms. The absence of regional variations of eNOS expression suggests that eNOS dysregulation in BAV aortas is the result of underlying genetic factors associated with BAV disease, rather than changes stimulated by hemodynamic alterations. These findings provide insight into the underlying mechanisms of aortic dilation in patients with a BAV.